Fertility Capability Classification - I. Shafnas; Anil Kumar; Altaf Kuntoji (Research Highlights in Agricultural Sciences Vol. 7, 2023)
The Fertility Capability Classification (FCC) system is a technical soil classification method that places a quantitative emphasis on physical and chemical aspects of soil that are crucial to managing soil fertility. This classification system was created to interpret the taxonomy of soil and other soil characteristics in a way that is directly applicable to plant growth and the sustainable production of crops. Based on quantitative topsoil properties and soil taxonomy, the method is an excellent place to start when addressing soil quality for the tropics. Understanding the resources and constraints of the land and allocating particular land units to uses that are not adversely impacted by the constraints provided by the land area are two ways that FCC contributes to the protection of land and soil resources for increasing health and productivity.